Case Study 2019; impact Of Pakistan And India War Conditions On Security Exchange Commission Of Pakistan - Islam, Aliya Tauqeer (Advances in Social Sciences Research Journal, 2019)
This paper inspects the connection among FDI and fear based oppression, utilizing information from 2008 to 2018-19. The word 'Psychological oppression' is a term commonly used to depict the greatest potential degrees of ill-conceived deeds or compulsions where the greater part of the populace is influenced and the most noteworthy level of monetary action is upset. In any case, this isn't the last and concurred meaning of the word psychological oppression. There is no single meaning of psychological warfare which is worthy to all. Therefore, Pakistan has extraordinarily endured socially, monetarily, and politically also. Contrasting the advantages of the war and the expense caused, we can securely presume that the expenses are a lot higher than the advantages of this war against fear based oppression. Finding demonstrates that because of increment in the quantity of psychological militant assaults outside financial specialist indicating negative enthusiasm to put cash in Pakistan.